Citizenship tests in five Countries: An expression of political liberalism? - Ines Michalowski (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
Engaging discussions on civic integration for immigrants, this comparison systematically analysis citizenship tests in the US, Austria, the UK, Germany, and the Netherlands. A central question discussed is whether these tests can be interpreted as assimilation, repressive liberalism or as a neutral instrument that changes its function according to the surrounding citizenship regime as some authors argue. The analysis has the surprising result that none of the hypotheses from the existing literature on civic integration can explain the content of all five citizenship tests. In particular I find that the characteristics of the surrounding citizenship regime are not a good predictor for the content of the respective citizenship tests: countries with rather restrictive citizenship regimes such as Austria or Germany have opted for a citizenship test with a liberal content that is comparable not only to the British but also to the US-American test. On the other hand the content of the Dutch citizenship test does not fully correspond to a Rawlsian definition of political liberalism although the Dutch citizenship regime is relatively open. Therefore I conclude that the formal character of a citizenship regime is only loosely connected with the national definition of citizenship as it is conveyed by the content of citizenship tests. It is not because civic integration requirements are obligatory and restrict the free will of future citizens that citizenship itself is defined in illiberal terms. – – Als Beitrag zu der Debatte über Integrationsanforderungen für Zuwanderer vergleicht diese Studie systematisch den Inhalt von Einbürgerungstests der USA, Österreichs, des Vereinigten Königreichs, Deutschlands und der Niederlande. Eine zentrale Frage ist, ob die Tests als Assimilation, repressiver Liberalismus oder neutrales Instrument, dessen Funktion erst durch den Charakter des jeweiligen Staatsangehörigkeitsregimes bestimmt wird, verstanden werden können. Überraschenderweise zeigt die Studie, dass keine der in der Literatur vertretenen Hypothesen den Inhalt aller fünf Einbürgerungstests erklären kann. Insbesondere wird deutlich, dass Länder mit einem eher restriktiven Staatsangehörigkeitsrecht wie Österreich und Deutschland Einbürgerungstests mit einem liberalen Inhalt eingeführt haben, der nicht nur dem britischen, sondern auch dem amerikanischen Test ähnelt. Andererseits entspricht der Inhalt des niederländischen Tests nicht vollständig einer Rawlsischen Definition des politischen Liberalismus, obwohl das niederländische Staatsangehörigkeitsrecht relativ offen ist. Deshalb komme ich zu der Schlussfolgerung, dass der formale Charakter eines Staatsangehörigkeitsregimes nur lose mit dem jeweiligen nationalen Verständnis von Bürgerschaft verbunden ist, wie es durch den Inhalt der Einbürgerungstests zum Ausdruck gebracht wird. Der obligatorische Charakter von Integrationsanforderungen, der den freien Willen zukünftiger Bürger einschränkt, besagt nicht, dass Bürgerschaft in illiberalen Termini definiert wird.
Keywords: 360; Citizenship test; naturalization; civic integration; USA; Austria; Netherlands; UK; Germany; Einbürgerungstests; Einbürgerung; Integrationsanforderungen; USA; Österreich; Niederlande; Vereinigtes Königreich; Deutschland